A Study of Factors and Influences Relationship to Exercise Behavior of the Elderly in Lishui City - Hong , Mei; Duangkam, Jakrin; Eakronnarongchai, Wiradee; Phiphithkul, Phunarat (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Exercise behavior in the elderly is crucial for maintaining physical health, cognitive function, and overall well-being. Regular physical activity helps prevent chronic diseases, improves mobility, and enhances mental health, contributing to a higher quality of life and independence in aging populations. This study aims to examine the influence of physical activity behavior among elderly individuals in Lishui City. The research specifically explores the role of individual health status, demographic characteristics (age, gender, and education level), sports skills, family support, and environmental factors such as the accessibility of sports facilities in shaping exercise habits in physical activity among older adults. Materials and Methods: The sample group of 497 elderly people using stratified random sampling was selected from 9 exercise points in 9 districts and counties of Lishui City. The questionnaire was from 10 expert people, and the reliability of the questionnaire with Cronbach’s Alpha coefficient was 0.73, indicating high confidence in the questionnaire. Data analysis was performed using frequency, percent, correlation coefficients, and Pearson’s, and survey data was performed using Kaplan-Meier Estimator & Cox Proportional Hazards Model. Results: The results indicate that exercise skills (fitness skills and perceived exercise efficacy) and environmental factors (such as family support) significantly impact the rate at which older adults develop and maintain exercise habits. Conclusion: This study identifies key factors influencing elderly exercise behavior in Lishui City, including physical, mental, social, and moral health, as well as sleep quality and diet. Age, gender, education, and economic status shape exercise participation, while fitness skills and family support significantly impact habit formation. Skill improvement enhances exercise efficiency, while family support fosters motivation and long-term adherence. The interaction between skill proficiency and social support plays a crucial role in accelerating and sustaining regular exercise habits among older adults.